Research on Economic Law Teaching Reform Based on Big Data. Issue 3 (October 2020) - Gu, Xiaoting
Abstract: The course of economic law, as a basic course of economics and management, plays an important role in the cultivation of students' vocational ability. It is also helpful to realize the cultivation of students' vocational ability, help them to set up a better view of employment and help them to establish their vocational view. At present, in the era of big data, more and more problems have emerged in the teaching of economic law for economic majors. Some experts and scholars put forward that the basic reform can be carried out according to their professional characteristics, pay attention to the analysis of typical cases of students in daily teaching, adopt diversified assessment standards, and constantly improve the teaching quality.